Organizing the Humanistic Curriculum with the Concept of Fitrah-Based Education - Susanto Susanto; Izzati Robbi Hamiyya (INTEGRATIA: Journal of Education, Human Development, and Community Engagement, 2023)
This paper aims to analyze the implementation of the Fitrah Based Education concept in organizing the humanistic curriculum. The method used in this study is a descriptive qualitative method with the type of research document/text study (literature study). This study uses primary data sources from books, journals, research, and documents that are relevant to this research. Data analysis in this study was carried out qualitatively using content analysis techniques with conceptual analysis. Based on the research findings, it is found that organizing the humanistic curriculum with the concept of Fitrah Based Education begins with: 1) determining the role of each educator. 2) assess the characteristics of each student, then determine the learning objectives through the initial indicators of each fitrah dimension as a reference. 3) carry out learning that can fulfill the eight aspects of fitrah in its activities. 4) Last, evaluate the learning process through observations and reflect on each fitnah's final indicators. The interesting point about this study is the classification of 8 Fitrah aspects in Fitrah Based Education as the basis for providing humanistic value to students. These eight aspects should be grown simultaneously in the learning process to fulfill the student's needs and build each student's character and knowledge according to the Islamic concept of human nature.